Self Efficacy and Resilience in Adolescent Drug Abusers - Wahyuni Wahyuni; Safira Senggo' Palayukan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to see the relationship between self-efficacy and resilience in adolescent victims of drug abuse in Makassar. The research method used is analytical descriptive research with a cross-sectional study approach. The sample in this study was selected by purposive sampling with a total of 120 respondents. The results of this study obtained a p value of 0.002 (<0.05) using the Fisher/s exact test. Conclusion, there is a relationship between self-efficacy and resilience in adolescent victims of drug abuse in Makassar. Keywords: Adolescents, Drugs, Resilience, Self-Efficacy.